Promoting Peer Assessment ’Learner to Learner’ Feedback in a Multilingual High School English First Additional Language Setting - Zano, Kufakunesu (Universitas Pendidikan Mandalika, 2022)
Feedback, further known as assessment in this research, is critical to learners’ growth and learning. This study is grounded in verbal and written peer experiences acquired throughout peer evaluation in a multilingual context. This study aims to determine the problems of Grade 11 EFAL learners with peer assessment and how to develop peer assessment practices in a multilingual setting at the high school level. There were 27 learners in the class. Designated three learners gave three demonstrations on various matters premised on a requisite Grade 11 literature set book and were graded by their classmates. The perspectives of the learners who were assigned to work in groups were elicited by requesting them to respond to open ended questions in writing after their classmates’ presentations. According to the findings, some peer assessments can be subjective depending on the bond between the assessor and the assessed. The learners had a natural feeling of inadequacy in their assessments. When giving feedback in a multilingual setting, it becomes important to give it in a language they are most comfortable with. Similarly, helping students relate new information from peers to the knowledge that they already have helps them to understand and organise information in meaningful ways.